Cenozoic moisture fluctuations on the northeastern Tibetan Plateau and association with global climatic conditions. (15th September 2020) - Sun, Yuanyuan; Liu, Jun; Liang, Yu; Ji, Junliang; Liu, Weiguo; Aitchison, Jonathan C.; Sun, Jimin; Lu, Jingfang; Song, Bowen; Xu, Yadong; Zhang, Kexin; Liu, Zhonghui
Graphical abstract: Highlights: δ 18 Ocarb and δ 13 Calk records from a >5, 000 m-thick sequence in the Qaidam Basin. Regional moisture fluctuations over the Cenozoic inferred. Linkage of moisture changes to global climate depends on the chosen chronology. Abstract: The Cenozoic history of aridification in the Asian interior is thought to be intimately linked to uplift of the Tibetan Plateau and long-term global cooling. How fluctuating climatic conditions influenced regional moisture levels during the Cenozoic remains largely unknown. To infer moisture changes, we present oxygen isotope values of carbonates (δ 18 Ocarb ) and carbon isotope values of long-chain n -alkanes (δ 13 Calk ) from a continuous geological section in the Qaidam Basin, northwestern China. The section spans most of the Cenozoic Era, from ~52 to 5 million years ago (Ma), based on conventional chronology, whereas recently a drastically revised chronology has placed its basal age at ~26 Ma. The association of moisture changes with global climate largely depends on the chosen chronology. With the revised chronology, our records are inconsistent with existing moisture records from the Asian interior and do not show clear association with global climatic conditions. However, with the conventional chronology, our δ 18 Ocarb record shows a long-term aridification trend over the Cenozoic, whereas the δ 13 Calk suggests reduced moisture levels during the Oligocene. Both records consistently show enhanced aridity, notably during the Oligocene, ~20–17 Ma and after ~13 Ma, which largely corresponded to relatively cool global periods. Our records thus suggest that global climatic conditions during the Cenozoic exerted more influence on the moisture levels in the Asian interior than previously thought, if the conventional chronology is correct. Our study also highlights the importance of constructing a reliable chronology in order to make an association of Cenozoic terrestrial records with global climate.